Using Strategies Elites Understand: Divestment as an Approach to Social Change. Issue 5 (20th October 2022) - Dizon, Jude Paul Matias; Harper, Jordan; Kezar, Adrianna
ABSTRACT: Over the past 50 years, student activists and community organizers on college campuses have advocated for divestment as a strategy to enact necessary change. These activists and organizers are often tasked to confront the higher education elite, such as trustees, with these demands. Higher education institutions will only continue to face immense pressures to be humane organizations with the public interest at its core. This article reviews the literature on divestment as a social activist strategy and its use in higher education. In addition to the political importance of divestment, reinvestment is emerging as a significant complement to activists' demands. We advance an argument for how divestment and reinvestment can inform a new paradigm for higher education finance to stimulate future activism.